Semi-Active Controllable Stiffness Engine Mount Utilizing Natural Rubber-Based Magnetorheological Elastomers - Mat Song, Rusdi; Mazlan, Saiful Amri; Johari, Norhasnidawani; Imaduddin, Fitrian; Abdul Aziz, Siti Aishah; Abd Fatah, Abdul Yasser; Ubaidillah, U. (Frontiers in Materials, 2022)
This study proposes the design and fabrication of natural rubber based magnetorheological elastomer (NR-MRE) engine mount as a new device in absorbing vibration originated from the automotive engine. The conceptual design was performed through simulation process using finite element method magnetics to analyze the magnetic field distribution. The simulation result had indicated that the device capable of generating an equivalent magnetic field density of 0.31 T at the effective area. The MRE was prepared by utilizing 60 wt% of carbonyl iron particles (CIPs) and filled the cavity using compression molding. The MRE compound was tested upon its basic mechanical properties while the MRE engine mounts were tested under static compression load at off- and on-state condition. It was observed that the compound possessed a good tensile strength for a load bearer matrix with an average of 12.65 MPa. Subsequently, the results of the static compression load had showed that the MRE engine mounts recorded an increase of 12% in force generated as compared to conventional engine mount at off-state condition. Meanwhile, at on-state condition of 2.4 A, the MRE engine mounts recorded an increased in force generated with 106%. The study has demonstrated that the proposed device can be one of the potential candidates for vibration control applications due to its stiffness controllability.